Will drivers for home energy efficiency harm occupant health? - Bone, Angie; Murray, Virginia; Myers, Isabella; Dengel, Andy; Crump, Derrick (Sage, 2010)
The UK government has committed to an 80% reduction in carbon emissions by 2050, with housing accounting for 27% of total current emissions. There are several drivers both to reduce emissions from homes and to reduce fuel poverty, promoting a range of building and behavioural measures in homes. The health benefits of warmer homes in winter have been described, but there has been less consideration of the potential negative impacts of some of these measures. We examine the changes in UK homes, and the possible consequences for health. The main concerns for health surround the potential for poor indoor air quality if ventilation is insufficient and the possible risks of overheating in heatwave conditions. This paper notes a limited evidence base and the need for further research on the health effects of energy-efficient homes, particularly with regard to ventilation.
Keywords: health homes energy efficiency indoor air quality heatwave